2019
DOI: 10.1002/fuce.201900087
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Carbon Supported PtCu Electrocatalysts for PEMFCs by in situ Supercritical Deposition Coupled with Electrochemical Dealloying

Abstract: Carbon aerogel and Vulcan supported PtCu electrocatalysts were prepared using the simultaneous and sequential in situ supercritical deposition (SCD) method in supercritical CO2 followed by thermal annealing and electrochemical dealloying. Before dealloying, annealed electrocatalysts prepared by simultaneous SCD had a more uniform PtCu composition in PtCu nanoparticles whereas electrocatalysts prepared by sequential SCD led to PtCu nanoparticles with Cu enrichment on the surface. Upon dealloying, PtCu/CA electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Secondly, it is necessary to determine, whether such de-alloyed PtCu x−y /C catalysts retain high stability and activity in ORR and MOR, which are characteristic of the previously studied alloyed PtCu x /C catalysts [27][28][29][30][31]. Note that uneven distribution of the doping component atoms in the "body" of the initial PtM nanoparticles obtained during the synthesis, as well as the changes in conditions of their de-alloying can apparently affect both the composition and activity/stability of the de-alloyed catalysts [21,22,[32][33][34][35]. Thus, the search for the best PtCu compositions and structures of bimetallic nanoparticles, selection of the optimal conditions for the transformation of alloyed PtCu x /C catalysts into a de-alloyed state, as well as the study of the de-alloyed PtCu x−y /C catalysts behavior, proves to be timely and relevant.…”
Section: Introductionmentioning
confidence: 58%
“…Secondly, it is necessary to determine, whether such de-alloyed PtCu x−y /C catalysts retain high stability and activity in ORR and MOR, which are characteristic of the previously studied alloyed PtCu x /C catalysts [27][28][29][30][31]. Note that uneven distribution of the doping component atoms in the "body" of the initial PtM nanoparticles obtained during the synthesis, as well as the changes in conditions of their de-alloying can apparently affect both the composition and activity/stability of the de-alloyed catalysts [21,22,[32][33][34][35]. Thus, the search for the best PtCu compositions and structures of bimetallic nanoparticles, selection of the optimal conditions for the transformation of alloyed PtCu x /C catalysts into a de-alloyed state, as well as the study of the de-alloyed PtCu x−y /C catalysts behavior, proves to be timely and relevant.…”
Section: Introductionmentioning
confidence: 58%
“…To characterize the structure of Pt nanoparticles, field release scanning electron microscopy, transmission electron microscopy, and X‐ray diffraction can be used 92 . Barim et al 93 suggested manipulated variables in the advanced decomposition process by in situ supercritical depositions (SCD) technique, associated with thermal annealing and electrochemical dealloying in supercritical CO 2 , such as increasing the temperature where the particle size of Pt increased regardless of the CA used. This indicated that the synthesis method and the parameters played are very important in the production of catalysts, and the average metal particle measurement control method can be applied to expand the supporting materials, which have various properties and characteristics.…”
Section: Current Limitations To Organic Aerogelmentioning
confidence: 99%
“…Co, Ni, Cu, Fe) exhibit an increased activity for the oxygen reduction reaction (ORR) and thus lead to a remarkable performance improvement of the corresponding membrane electrode assembly (MEA) in PEMFCs compared to pure Pt/C based systems. [6][7][8][9][10][11] Advantageously, the dilution of the particle core with these 3d transition metals simultaneously leads to a reduction in the total amount of noble metal. 12 However, the use of these alloying transition metals also comes with two major disadvantages: the higher complexity of the overall catalyst, e.g.…”
Section: Introductionmentioning
confidence: 99%